Vibration Analysis of Multilink Manipulators Based on Timoshenko Beam Theory - Carmelo di Castri; Arcangelo Messina (Journal of Robotics)
Timoshenko's theory is adopted in order to accurately describe the freely vibrating dynamics of a multilink flexible manipulator. It is herein presented an analytical modelling strategy that extends previous works through a more refined model which accounts for elastic complicating effects along with lumped inertial loads which are typically mounted on joints of manipulators; in this regard, more accurate results are provided. The eigenproblem is presented from an analytical point of view through a matrix formulation, thus providing an essentially closed formula. Apart from the limitations of the implementing calculator, the formulation can take into account an arbitrary number of links in an arbitrary settled configuration, thus allowing relevant analytical analysis and avoiding the need to recur to nonimmediate numerical schemes. Once the analytical model is introduced, solutions are compared to both those achieved by previous models and those obtained by a finite elements method.